Supervisory control for conventional unitary air conditioning system - Morrison Buah, Lorothy (2012)
The Supervisory control for conventional unitary air conditioning system is conceptually designed based on Programmable Logic Control (PLC) system. The advantage of PLC system is that it allows online monitoring continually and updates or modification can be performed interactively. This supervisory mode is applied to the conventional unitary air conditioner to avoid the frequent interruption or adjustment of the fan speed or temperature set point by users normal practice which has contributed to the surge of energy consumption due to the frequent on/off of the compressor. Three experiments have been performed at different control methods to simulate user’s daily practice. The first control method is the Variable Set point with high speed fan, the second control method is the Fixed Set point with high speed fan and the third control method is a Supervisory Control; a fixed set point with variable fan speed. The experiments have been conducted for eight (8) hours and the statistic data of accumulated energy consumption based on one unitary air conditioner with capacity of 1 Horse Power are acquired and sampled at the time interval of 30 minutes for the analysis. From these experiments, the supervisory control has consumed 4.2 kWh per day which is 82.35% compared to normal consumption of 5.1 kWh. This result translated into 0.9 kWh or 17.65% of total energy saving per day. The consistency of the air compressor operation in this control method has become a major factor in achieving indoor temperature steadiness whilst improving the energy savings.